2009
DOI: 10.1128/iai.01184-08
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Characterization of a Novel Type III Secretion System in trh -Positive Vibrio parahaemolyticus Strain TH3996 Reveal Genetic Lineage and Diversity of Pathogenic Machinery beyond the Species Level

Abstract: Vibrio parahaemolyticus is a bacterial pathogen causative of food-borne gastroenteritis. Whole-genome sequencing of V. parahaemolyticus strain RIMD2210633, which exhibits Kanagawa phenomenon (KP), revealed the presence of two sets of the genes for the type III secretion system (T3SS) on chromosomes 1 and 2, T3SS1 and T3SS2, respectively. Although T3SS2 of the RIMD2210633 strain is thought to be involved in human pathogenicity, i.e., enterotoxicity, the genes for T3SS2 have not been found in trh-positive (KP-ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
183
0
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 147 publications
(197 citation statements)
references
References 33 publications
12
183
0
2
Order By: Relevance
“…All strains were tested for the presence of type III secretion system (T3SS) genes specific to T3SS1, T3SS2␣, and T3SS2␤ by using primers described previously (31,32). Strain TX2103 was used as a positive control for T3SS␣ and strain AQ4037 for T3SS␤ (31).…”
Section: Methodsmentioning
confidence: 99%
“…All strains were tested for the presence of type III secretion system (T3SS) genes specific to T3SS1, T3SS2␣, and T3SS2␤ by using primers described previously (31,32). Strain TX2103 was used as a positive control for T3SS␣ and strain AQ4037 for T3SS␤ (31).…”
Section: Methodsmentioning
confidence: 99%
“…Other studies (19)(20)(21) have reported that the tdh gene is encoded and co-regulated with T3SS2a genes, and that the T3SS2b genes have been detected in trh-positive strains. Moreover, all isolates contain T3SS1 (19,20).…”
Section: Discussionmentioning
confidence: 99%
“…T3SS: We also examined T3SS genes as potential indicators of virulence by PCR assays according to previously published studies (19,21) (Table 1). The targeted genes were VP1670, VP1686, VP1689, and VP1694 as T3SS1 genes, VPA1327, VPA1335, VPA1339, and VPA1362 as T3SS2a genes, and vscS2, vscC2, vopC, and vopB2 as T3SS2b genes.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, in addition to CT, T3SS in V. cholerae is another possible virulence determinant. The T3SS gene cluster is distributed among various non-O1, non-O139 strains (8,12) and a phylogenetic analysis of T3SS-related genes implied horizontal gene transfer of a T3SS gene cluster among Vibrio species (13,14). Up to now, however, there has been no experimental evidence of horizontal transfer of the T3SS-related genes.…”
mentioning
confidence: 99%